A Study of Political Language on The Fiscal Policy Discourse of Indonesia's Minister of Finance in 2025 - Purnamasari, Jelita; Nurrokhmah, Luluk Endang; Hastuti, Hepi (The Sunan Ampel Review of Political and Social Sciences, 2025)
Fiscal communication plays a crucial role in shaping public trust, promoting transparency, and reinforcing the legitimacy of government actions. Despite its significance, existing studies often emphasize macroeconomic performance rather than the rhetorical strategies that build credibility and empathy between policymakers and the public. This study investigates the rhetorical and linguistic strategies employed by Indonesian Finance Minister Purbaya Yudhi Sadewa during the crucial transitional period following his appointment in 2025, amid growing fiscal legitimacy challenges and public skepticism. The research focuses on how Minister Purbaya strategically constructed and communicated Indonesia’s fiscal narrative to regain public trust, stabilize perceptions of economic governance, and reinforce the credibility of fiscal policy after the leadership change. Using a qualitative descriptive method with a rhetorical and linguistic discourse analysis approach, the research examines selected public speeches and media statements delivered from his inauguration to October 2025. The analysis reveals that Purbaya’s fiscal communication emphasized clarity, empathy, and accountability, supported by rhetorical devices such as ethos, pathos, logos, metaphorical framing, and pronoun choice. These elements collectively simplified complex fiscal issues, humanized economic discourse, and fostered a sense of shared responsibility between the government and citizens. The findings indicate that effective fiscal communication requires not only technical expertise and data accuracy but also emotional resonance and ethical awareness. The study concludes that rhetorical competence is a vital aspect of fiscal governance, turning policy communication into a bridge of trust that strengthens both public confidence and the legitimacy of fiscal policy.